ChemInform Abstract: Tandem Intramolecular Diels—Alder/1, 3‐Dipolar Cycloaddition Cascade of 1, 3, 4‐Oxadiazoles: Initial Scope and Applications. Issue 17 (April 2016) - Sears, Justin E.; Boger, Dale L.
Abstract: Review: 78 refs.